The Principle of Common but Differentiated Responsibilities - Cerda Dueñas, Carlos (Revista Tribuna Internacional, 2016)
This article analyzes the efforts of Middle Income Countries to establish the principle of “Common but Differentiated Responsibilities” in international development law. The article also reviews the historical progress of Common but Differentiated Responsibilities from its origins in the economic ground, its transition to the environment law and the pursuit of its legal entry into the issue of international development cooperation. Developing Countries, especially the ones categorized as Middle Income Countries look for the recognition of this principle due they have high poverty rates and inequality levels and currently do not receive or receive less official development aid, but overall, because they are being pressured to act as donors and assume wider responsibilities in development.